(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In Shakespeare’s tragedies, madness is always related to death and murder. The playwright’s treatment of the theme, however, applies more to the dark and tragic experience of madness of the fifteenth century than to the critical and moral approach to unreason which was soon to abolish the previous views and which developed in his own epoch. For instance, in the latter years of the sixteenth century, “the social madness of demonology began to wane and was replaced by a different perception of the disturbed”.4 In King Lear, however, Edgar’s use of the medieval friends still testifies to that tragic experience of unreason of the fifteenth and previous centuries. Foucault very well remarks that the experience of madness in literature and art seems to have been extremely coherent, but that there was no continuity in such themes. Indeed, in the early years of the Renaissance, word and image begin to dissociate in their treatment of insanity, and the Gothic symbols of the Middle Ages, once so rich in spiritual significance, now become images of madness. In thee fantastic figures of nightmare, the concepts of animality, long established in the medieval mind, are now reversed. The beast is set free from the moral and mystic world of legend that it had inhabited in the Middle Ages. It becomes the secret nature of man. “Animality has escaped domestication by human symbols and values; and it is animality that reveals the dark rage, the sterile madness that lie in men’s hearts”.